Given the ODE
(x - 1) y'' + y' = 0
we assume a solution of the form
![y(x) = \displaystyle \sum_(n=0)^\infty c_n x^n](https://img.qammunity.org/2023/formulas/mathematics/college/1s1lva0g88j0t29spyiivurt9g2yvo0btd.png)
with derivatives
![y'(x) = \displaystyle \sum_(n=0)^\infty n c_n x^(n-1) = \sum_(n=0)^\infty (n+1) c_(n+1) x^n](https://img.qammunity.org/2023/formulas/mathematics/college/teuvh07ozz7v3x6lz42f5hmo8p9kc0n1ei.png)
![y''(x) = \displaystyle \sum_(n=0)^\infty (n+1) n c_(n+1) x^(n-1) = \sum_(n=0)^\infty (n+2)(n+1) c_(n+2) x^n](https://img.qammunity.org/2023/formulas/mathematics/college/5wab2c16cp545d5n2gjtr5hrbu4dx71fdk.png)
Substituting these series into ODE gives
![\displaystyle (x - 1) \sum_(n=0)^\infty (n+2)(n+1) c_(n+2) x^n + \sum_(n=0)^\infty (n+1) c_(n+1) x^n = 0](https://img.qammunity.org/2023/formulas/mathematics/college/ozdehf8fp3o4tqgbx1m13fudg6whj9oz4v.png)
![\displaystyle \sum_(n=0)^\infty (n+2)(n+1) c_(n+2) x^(n+1) - \sum_(n=0)^\infty (n+2)(n+1) c_(n+2) x^n + \sum_(n=0)^\infty (n+1) c_(n+1) x^n = 0](https://img.qammunity.org/2023/formulas/mathematics/college/1mgdqb1iqpjfgcrkj0d5kbfvnpohr7gu0k.png)
![\displaystyle \sum_(n=1)^\infty (n+1)n c_(n+1) x^n - \sum_(n=0)^\infty (n+2)(n+1) c_(n+2) x^n + \sum_(n=0)^\infty (n+1) c_(n+1) x^n = 0](https://img.qammunity.org/2023/formulas/mathematics/college/6oz3ar3akaupw95f19bcyh4pq0x241la4z.png)
![\displaystyle \sum_(n=1)^\infty \bigg((n+1)n c_(n+1) - (n+2)(n+1) c_(n+2) + (n+1) c_(n+1)\bigg) x^n - 2c_2 + c_1 = 0](https://img.qammunity.org/2023/formulas/mathematics/college/4opz81texjn2cps72gwtxir74ctsxlvycl.png)
![\displaystyle \sum_(n=1)^\infty \bigg((n+1)^2 c_(n+1) - (n+2)(n+1) c_(n+2)\bigg) x^n - 2c_2 + c_1 = 0](https://img.qammunity.org/2023/formulas/mathematics/college/b3j0zeost0hwpdqz4dqcibosvugud0yq7o.png)
![\displaystyle \sum_(n=0)^\infty \bigg((n+1)^2 c_(n+1) - (n+2)(n+1) c_(n+2)\bigg) x^n = 0](https://img.qammunity.org/2023/formulas/mathematics/college/bicejbmf7hz9hrcfwhgdqw15p3ola9dalf.png)
Then the coefficients
are given recursively by
![(n+1)^2 c_(n+1) - (n+2)(n+1) c_(n+2) = 0](https://img.qammunity.org/2023/formulas/mathematics/college/j0c7awfwu4t91n68czid6wwa4aexyfyelu.png)
for all n ≥ 0, or equivalently,
![c_(n+2) = (n+1)/(n+2) c_(n+1)](https://img.qammunity.org/2023/formulas/mathematics/college/18mw4o26fdv2cuuhmi2qy5o02oaiuzk5t1.png)
which most closely resembles the second choice.